PENERAPAN PELATIHAN KETERAMPILAN SOSIAL DAN EMOSI UNTUK MENGURANGI AGRESIFITAS PADA ANAK DENGAN BORDERLINE INTELLECTUAL FUNCTIONING - Aina, Qory; Savitri, Luh Surini Yulia (JURNAL PSIKOLOGI INSIGHT, 2020)
This research was aimed to investigate effectiveness of implementation of social and emotional skills training to reduce aggressiveness on child with borderline intellectual functioning (BIF). The participant was a 7 years old boy who was diagnosed having BIF that complained having difficulty to regulate his emotion when he was angry. The training program was adapted from Friendship Group Program that developed by Bierman et al. (2017), yet implemented in individual setting and adjusted to the child needs. In this program, researchers involved parent in the sessions and provided tasks to encourage him to practice the skills at his natural setting. It was single-subject design research to examine cause-effect relationship on the program deliver. The success of program implementation was evaluated qualitatively using interview, observation, and task evaluation; and quantitatively by comparing the score of Child Behavioral Checklist (CBCL) on social competence, social problem, and aggression problem. The result indicated that there were increase on social and emotional skills, and decrease on aggressiveness behavior on child with BIF.